Positive surgical margins in nephron-sparing surgery: risk factors and therapeutic consequences - Steinestel, Julie (World J Surg Oncol, 2014)
The increased use of nephron-sparing surgery to treat localized renal cell carcinoma (RCC) lends weight to the question of the value of microscopically positive surgical margins (PSM) in cases with a tumor bed macroscopically free of residual tumor. The aim of this article is to highlight the data available on risk factors for PSM, their clinical relevance, and possible therapeutic consequences. For this purpose, publications on the incidence and relevance of PSM after partial nephrectomy from the last 15 years were examined and evaluated. We summarize that PSM are generally rare, regardless of the surgical procedure, and are seen more often in connection with an imperative indication for nephron-sparing surgery as well as a central tumor location. Most studies describe that PSM lead to a moderate increase in the rate of local relapses, but no study has thus far been able to demonstrate an association with shorter tumor-specific overall survival. Intraoperative frozen section analysis had no positive influence on the risk of definite PSM in most trials. Therefore, we conclude that PSM should definitely be avoided. However, in cases with a macroscopically tumor-free intraoperative resection bed, they should lead to close surveillance of the affected kidney and not to immediate (re)intervention.